Papvimochneshwar Temple - Mumbai Archive Project Team (Jio Institute, 2024)
Papvimochneshwar Temple was established on August 18, 1904, and is dedicated to Lord Shiva. The temple is the focal point of Maha Shivaratri celebrations by the Koli community, which take place annually on the 14th night of the dark fortnight in the month of Phalguna (February–March).